Glutamate-induced obesity leads to decreased sperm reserves and acceleration of transit time in the epididymis of adult male rats - Fernandes, Glaura S. A.; Arena, Arielle C. [UNESP]; Campos, Kleber E.; Volpato, Gustavo T.; Anselmo-Franci, Janete A.; Damasceno, Débora Cristina [UNESP]; Kempinas, Wilma G. [UNESP] (Biomed Central Ltd., 2012)
Background: Given the established fact that obesity interferes with male reproductive functions, the present study aimed to evaluate sperm production in the testis and storage in the epididymis in a glutamate-induced model of obesity.Methods: Male rats were treated neonatally with monosodium glutamate (MSG) at doses of 4 mg/kg subcutaneously, or with saline solution (control group), on postnatal days 2, 4, 6, 8 and 10. on day 120, obesity was confirmed by the Lee index in all MSG-treated rats. After this, all animals from the two experimental groups were anesthetized and killed to evaluate body and reproductive organ weights, sperm parameters, plasma hormone levels (FSH, LH and testosterone), testicular and epididymal histo-morphometry and histopathology.Results: Significant reductions in absolute and relative weights of testis, epididymis, prostate and seminal vesicle were noted in MSG-treated animals. In these same animals plasma testosterone and follicle-stimulating hormone (FSH) concentrations were decreased, as well as sperm counts in the testis and epididymis and seminiferous epithelium height and tubular diameter. The sperm transit time was accelerated in obese rats. However, the number of Sertoli cells per seminiferous tubule and stereological findings on the epididymis were not markedly changed by obesity.Conclusions: Neonatal MSG-administered model of obesity lowers sperm production and leads to a reduction in sperm storage in the epididymis of adult male rats. The acceleration of sperm transit time can have implications for the sperm quality of these rats.
Keywords: Obesity; Monosodium glutamate; Epididymis; Testosterone; Sperm; Rat